Digital control systems - Benjamin C. Kou (Oxrord University press, 1996)
An introductory text for a senior or graduate course on digital control systems, this text covers the theory and applications of digital control systems, assuming a knowledge of matrix algebra, differential equations, Laplace transforms and the basic principles of continuous-data control systems. Many subjects are new to the Second Edition, most importantly design topics such as disturbance rejection, sensitivity considerations, and zero-ripple deadbeat-response design